The World's Smallest Bible, Hall of Religion
Printed in 1895 by David Bryce & Son, Glasgow, Scotland. Brought to America by J. Francis Ruggles, internationally known rare Bible collector, whose seal is in this book. Book contains 520 numbered pages, is less than 1/4 inch thick, and has 181,253words - or 838,380 letters on its printed pages. One printed page is about 1-3 the size of a postage stamp by comparison. Parchment bound - sewed with silk thread. Required nearly 4 years to complete.